Politeness Strategy and Principles Used in Conversation on Green Book Film - Yosia Rajagukguk; Erika Sinambela; Arsen Nahum Pasaribu (CV. Inara, 2021)
The aims of this study is to examine the Politeness Principles and Politeness Strategy in the context of the film Green Book. This is a qualitative study, and the data are analyzed descriptively. The data was collected and shown in a table, which included turn-taking, speech, and speakers. This study's findings revealed four key points. To begin, Brown and Levinson's theory suggested three politeness concepts and four politeness strategies: positive face, negative face, and face threatening-acts as politeness principles, and positive politeness strategy, negative politeness strategy, bald on-record, offrecord. Second, the politeness strategy On-record, off-record, pessimistic face, good face, they were both bald. Finally, the most common forms of politeness values were negative face (45.5%) and negative politeness technique (36.4%). Finally, the most strong of negative politeness accounted for 36.4% of all politeness strategies, followed by optimistic politeness and off-record politeness strategies, both accounting for 27.3%, and bald on-record politeness accounting for 18.2%